RESOURCE EVALUATION - KLOEPFER B (Tufts Archival Research Center, 2007)
Confidential; Memorandum from Bill Kloepfer to Samuel D. Chilcote Jr. regarding resources of the State Activities Department in addressing tobacco related issues.